2023
DOI: 10.1097/wno.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of International Classification of Diseases Codes for Identifying Acute Optic Neuritis

Abstract: Background: The accuracy of International Classification of Diseases (ICD) codes for identifying cases of acute optic neuritis (aON) is not known. A prior study reported 61% accuracy for ICD code plus MRI consistent with aON within 2 months. This study determined accuracy for ICD code plus MRI within 2 months regardless of results. Methods: Retrospective chart review was conducted using a medical record research repository of a tertiary care institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Manual review is not practical for extremely large databases, and the lack of a specific ICD-10 code for NAION (as identified by Hamedani et al) would be a severe hindrance for any large study. Emerging algorithms would improve the accuracy of diagnostic coding in larger studies but would not attain the precision of a manual review and might not provide sufficient accuracy to establish a statistical association between use of a drug and occurrence of a relatively uncommon disorder like NAION.…”
Section: Discussionmentioning
confidence: 99%
“…Manual review is not practical for extremely large databases, and the lack of a specific ICD-10 code for NAION (as identified by Hamedani et al) would be a severe hindrance for any large study. Emerging algorithms would improve the accuracy of diagnostic coding in larger studies but would not attain the precision of a manual review and might not provide sufficient accuracy to establish a statistical association between use of a drug and occurrence of a relatively uncommon disorder like NAION.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of International Classification of Diseases (ICD) billing code accuracy have shown that common conditions (e.g., cataract, diabetic retinopathy, and age-related macular degeneration) tend to have a greater predictive value [5]. In contrast, ICD codes for less common diagnoses (e.g., neuro-ophthalmic, ocular inflammatory, pediatric eye diagnoses) may be less accurate [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%